Chromatic Number of the Corona Product of Complete Graph and Star Graph - Asmarani, Mustika; Yulianti, Kartika; Mulyaning Asih, Endang Cahya (Jurnal MSA ( Matematika dan Statistika serta Aplikasinya), 2025)
In this paper, we determine the chromatic number of the corona product of complete graph K_n and star graph K_1,m. Determination of the chromatic numbers is done by observing patterns, constructing conjectures, and proving them formally. We found that the chromatic number of the corona product of complete graph K_n and star graph K_1,m is χ(K_nK_1,m)={matrix3, n=1,2 , n=3,4,…, k matrix., and the chromatic number of the corona product of star graph K_1,m and complete graph K_n is χ(K_1,mK_n)=n+1, n=1,2,…, k. Furthermore, using Matlab software, a program is created to visualize the coloring of the vertices based on the formula that has been obtained.